Psychotherapeutic depression interventions adapted for sexual and gender minority youth: A systematic review of an emerging literature. Issue 4 (2nd October 2019) - Sheinfil, Alan Z.; Foley, Jacklyn D.; Ramos, Jeremy; Antshel, Kevin M.; Woolf-King, Sarah E.
Abstract: Sexual and gender minority youth (SGMY) are disproportionately affected by mental health problems, including depression and suicidality. Recently, there has been increased interest in developing and adapting evidence-based treatments for depressive symptoms tailored to address the unique issues facing SGMY. This is the first systematic review of interventions targeting depressive symptoms that have been adapted for SGMY populations. Findings from these studies provide evidence in support of the feasibility, acceptability, and preliminary efficacy for SGM-informed interventions for the treatment of depressive symptoms. Fully powered randomized controlled trials are needed to determine the efficacy of these adapted treatments prior to dissemination.